Pengembangan E-Modul Interaktif Analisis Puisi Arab Klasik Berbasis Pjbl Menggunakan Platform Digital - Perdana, Dyah Adila (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to develop and evaluate an interactive e-module for classical Arabic poetry analysis based on Project-Based Learning (PjBL) using a digital platform, as well as to assess its effectiveness in improving students’ literary analysis competence. The research employed a Research and Development (R&D) design, consisting of needs analysis, module design, expert validation, limited trials, and effectiveness evaluation. Validation was conducted by experts in Arabic literature and educational media, while the trial phase involved students as respondents to assess usability, media attractiveness, and learning engagement. The findings indicate that the developed e-module demonstrates high content and design validity, featuring materials aligned with the principles of classical Arabic poetry, clear PjBL project instructions, and multimedia elements that support interactive learning. Students’ responses to the module were highly positive; the module enhanced motivation, active engagement, and collaboration during project implementation. Its effectiveness is further reflected in students’ improved ability to identify intrinsic elements of poetry, interpret symbolism, understand cultural context, and construct coherent and reflective analytical arguments. Challenges such as technical constraints and adaptation to PjBL methods were mitigated through instructor guidance and module refinement. Thus, the interactive PjBL-based e-module proves effective as an innovative learning medium for the analysis of classical Arabic poetry, while also strengthening students’ analytical skills, critical thinking, and collaboration. This module serves as a relevant and sustainable technology-based learning model for Arabic literature education in the digital era.